Plasma Cortisol Concentrations and Perceived Anxiety in Response to On-Sight Rock Climbing - Draper, N.; Dickson, T.; Fryer, S.; Blackwell, G.; Winter, D.; Scarrott, C.; Ellis, G. (International Journal of Sports Medicine, 2012)
Previous research suggested plasma cortisol concentrations in response to rock climbing have a cubic relationship with state anxiety and self-confidence. This research, however, was conducted in a situation where the climbers had previously climbed the route. The purpose of our study was to examine this relationship in response to on-sight climbing. Nineteen (13 male, 6 female) intermediate climbers volunteered to attend anthropometric and baseline testing sessions, prior to an on-sight ascent (lead climb or top-rope) of the test climb (grade 19 Ewbank/6a sport/5.10b YDS). Data recorded included state anxiety, self-confidence and cortisol concentrations prior to completing the climb. Results indicated that there were no significant differences in state anxiety, self-confidence and plasma cortisol concentration regardless of the style of ascent (lead climb or top-rope) in an on-sight sport climbing context. Regression analysis indicated there was a significant linear relationship between plasma cortisol concentrations and self-confidence (r= − 0.52, R2=0.267, p=0.024), cognitive (r=0.5, R2=0.253, p=0.028), and somatic anxieties (r=0.46, R2=0.210, p=0.049). In an on-sight condition the relationships between plasma cortisol concentrations with anxiety (cognitive and somatic) and self-confidence were linear.
Keywords: rock climbing; plasma cortisol concentration; psychophysiology; lead climbing; top-roping